The heat shock protein HSP70 and heat shock cognate protein HSC70 contribute to antimony tolerance in the protozoan parasite Leishmania - Brochu, Christian (Cell Stress Society International, 2004)
Antimony-containing drugs are still the drugs of choice in the treatment of infections caused by the parasite Leishmania. Resistance to antimony is now common in some parts of the world, and several mechanisms of resistance have been described. By transfecting cosmid banks and selecting with potassium antimonyl tartrate (SbIII), we have isolated a cosmid associated with resistance. This cosmid contains 2 copies of the heat shock protein 70 (HSP70) and 1 copy of the heat shock cognate protein 70 (HSC70). Several data linked HSP70 to antimony response and resistance. First, several Leishmania species, both as promastigotes and amastigotes, increased the expression of their HSP70 proteins when grown in the presence of 1 or 2 times the Effect Concentration 50% of SbIII. In several mutants selected for resistance to either SbIII or to the related metal arsenite, the HSP70 proteins were found to be overexpressed. This increase was also observed in revertant cells grown for several passages in the absence of SbIII, suggesting that this increased production of HSP70 is stable. Transfection of HSP70 or HSC70 in Leishmania cells does not confer resistance directly, though these transfectants were better able to tolerate a shock with SbIII. Our results are consistent with HSP70 and HSC70 being a first line of defense against SbIII until more specific and efficient resistance mechanisms take over.